Nuclear Lactate Dehydrogenase A Resists Cardiomyocyte Cell Cycle Arrest Induced by Oxidative Stress - Mengfei Cao; Jie Luo; Kewei Fu; Yao Xu; Yinyu Wang; Junying Duan; Rui Chen; Wei Yuan (Journal of Cardiovascular Development and Disease, 2025)
A sudden increase in ambient oxygen concentration after birth forces the metabolic switch from anaerobic glycolysis to oxidative phosphorylation, which contributes to the rapid decline of cardiomyocyte proliferation. Lactate dehydrogenase A (LDHA), a metabolic enzyme normally localized in the cytoplasm, has been reported to regulate cardiomyocyte proliferation via inducing metabolic reprogramming. Nuclear LDHA has been observed in multiple proliferative cells, whereas the role of LDHA nuclear translocation in cardiomyocyte proliferation remains unresolved. Here we found that the expression of nuclear LDHA was induced both in the infarct area of myocardial infarction (MI) in mice and hypoxic cardiomyocytes in vitro. Mechanically, mild hypoxia prompted metabolic reprogramming which motivated cardiomyocyte proliferation by alleviating reactive oxygen species (ROS), while severe hypoxia coincided with oxidative stress that induced cardiomyocyte cell cycle arrest. Interestingly, LDHA nuclear translocation in cardiomyocytes occurred in response to oxidative stress, and blocking of nuclear LDHA resulted in elevated ROS generation. Collectively, our findings uncover a non-canonical role of nuclear LDHA in maintaining redox balance and resisting cardiomyocyte cell cycle arrest.